Loganin attenuates neuroinflammation after ischemic stroke and fracture by regulating α7nAChR‐mediated microglial polarization. Issue 4 (13th January 2023) - Huo, Kang; Xu, Jing; Ma, Kaige; Wang, Jianyi; Wei, Meng; Zhang, Meng; Guo, Qinyue; Qu, Qiumin
Abstract: Fracture in acute stage of ischemic stroke can increase inflammatory response and enhance stroke injury. Loganin alleviates the symptoms of many inflammatory diseases through its anti‐inflammatory effect, but its role in ischemic stroke and fracture remains to be explored. Here, mice were handled with permanent middle cerebral artery occlusion (pMCAO) followed by tibial fracture 1 day later to establish a pMCAO+fracture model. Loganin or Methyllycaconitine (MLA, a specific a7nAchR inhibitor) were intragastrically administered 2 or 0.5 h before pMCAO, respectively. And mouse motor function and infarct volume were evaluated 3 days after pMCAO. We found that loganin alleviated the neurological deficit, cerebral infarction volume, and neuronal apoptosis (NeuN + TUNEL + ) in mice with pMCAO+fracture. And loganin suppressed pMCAO+fracture‐induced neuroinflammation by promoting M2 microglia polarization (Iba1 + CD206 + ) and inhibiting M1 microglia polarization (Iba1 + CD11b + ). While administration with MLA reversed the protective effect of loganin on pMCAO+fracture‐induced neurological deficit and neuroinflammation. Next, LPS was used to stimulate BV2 microglia to simulate pMCAO+fracture‐induced inflammatory microenvironment in vitro. Loganin facilitated the transformation of LPS‐stimulated BV2 cells from M1 pro‐inflammatory state (CD11b + ) to M2 anti‐inflammatory state (CD206 + ), which was antagonized by treatment with MLA. And loganin induced autophagy activation in LPS‐stimulated BV2 cells by activating a7nAchR. Moreover, treatment with rapamycin (an autophagy activator) neutralized the inhibitory effect of MLA on loganin induced transformation of BV2 cells to M2 phenotype. Furthermore, BV2 cells were treated with LPS, LPS + loganin, LPS + loganin+MLA, or LPS + loganin+MLA+ rapamycin to obtain conditioned medium (CM) for stimulating primary neurons. Loganin reduced the damage of primary neurons caused by LPS‐stimulated BV2 microglia through activating a7nAchR and inducing autophagy activation. In conclusion, loganin played anti‐inflammatory and neuroprotective roles in pMCAO + fracture mice by activating a7nAchR, enhancing autophagy and promoting M2 polarization of microglia.